圧迫・せん断力発生時の毛細血管血流挙動観察装置の開発 - 柴田, 雅廣; 花園, 祥一; 米田, 隆志 (Transactions of Japanese Society for Medical and Biological Engineering, 2015)
Normally, when pressure ulcer occurred, pressure and sharing force are increased on the surface of tissues and this condition makes the blood capillary become blockage. However, we don't know how much pressure and sharing force influence on tissues and capillary. Therefore, in this study is analyzing it. This research, embarked on the development of a device that is deployed in the observation and evaluation of blood flow behavior in capillary. The device is composed of a microscope to record capillary and mechanisms to apply pressure and sharing force. The device recognizes red blood cells from recorded motion picture by microscope to measure the blood flow rate and the displacement of the capillary quantitatively. And we make the method to measure them. We use contrast between capillary and skin to discriminate red blood cells on motion picture. The method is gray scale and normalization. For this method, we can increase the contrast. Furthermore, we discriminate red blood cells by threshold processing. We can estimate the blood flow rate by the speed of flow, and the displacement of capillary by the distance of the inter-frame.